Short term effect of tetrahydrocurcumin on adipose angiogenesis in very high-fat diet-induced obesity mouse model - Yoysungnoen, Bhornprom; Srisawat, Umarat; Piyabhan, Pritsana; Duansak, Naphatsanan; Sookprasert, Nattapon; Mathuradavong, Nakorn; Poomipark, Natwadee; Munkong, Narongsuk; Tingpej, Pholawat; Changtam, Chatchawan (Frontiers in Nutrition, 2023)
Tetrahydrocurcumin (THC) has been shown to possess anti-angiogenic activities. This study aims to investigate the effects of THC on adipose angiogenesis and expression of angiogenic factors that occurs in 60% high-fat diet-induced obese mice. Male ICR mice were randomly divided into 3 groups: mice fed with a low-fat diet (LFD group); mice fed with very high fat diet (VHFD group), and mice fed with VHFD supplemented with THC ( 300 mg/ kg/ day orally) (VHFD+THC treated group) for 6 weeks. Body weight (BW), food intake, fasting blood sugar (FBS), lipid profiles and visceral fats weight (VF) were measured. The microvascular density (MVD), TNF-α, VEGF, MMP-2 and MMP-9 expressions were evaluated. The VHFD group had significantly increased total cholesterol, triglyceride, food intake, BW, VF, VF/BW ratio, adipocyte size and the number of crown-liked structures as compared to LFD group. THC supplementation markedly reduced these parameters and adipocyte hypertrophy and inflammation in white adipose tissues. MVD, TNF-α, VEGF, MMP-2 and MMP-9 were overexpressed in the VHFD group. However, THC supplementation decreased MVD and reduced expression of TNF-α, VEGF, MMP-2 and MMP-9. In conclusion, THC suppressed angiogenesis in adipose tissue by the downregulation of TNF-α, VEGF, MMP-2 and MMP-9. With its effects on lipid metabolism as well as on food consumption, THC could contribute to lower visceral fat and body weight. Overall, our study demonstrated the potential benefit of THC in mitigating obesity and associated metabolic disorders along with elucidated the suppression of adipose angiogenesis as one of its underlying mechanisms.